PROBLEMATIKA KETERAMPILAN BERBICARA DALAM BAHASA JERMAN SISWA KELAS XI SMA ISLAM AL-AZHAR 12 MAKASSAR - Firawati Firawati; Ade Yolanda; Prasuri Kuswarini (Bajang Institute, 2023)
students at SMA Islam Al-Azhar 12 Makassar. This research is a survey Research using a qualitative approach with descriptive research methods, which aims to get an overview of the problems with students' speaking skills in German for class XI SMA Islam Al-Azhar 12 Makassar. The subjects of this study were 22 students in class XI at SMA Islam Al-Azhar 12 Makassar. Data collection techniques used in this study were class observation, teacher interviews, and open and closed questionnaires. The results of this study indicate that the problem of speaking skills is influenced by two factors: internal factors (vocabulary, conjugation, ideas, sentence structure, pronunciation, shyness, and laziness) and external factors (means). The main challenge in speaking German is the very small vocabulary and the influence of other foreign languages.